Re-mapping the territory: an analysis of literacy intervention provision for primary students in five Australian states. Issue 2 (2nd July 2020) - Quick, Joanne
ABSTRACT: Literacy interventions are a common educational response for supporting students with literacy difficulties. Australian schools historically offered such programs, , though recent studies were not found in the research literature. This paper reports on school-level and literacy intervention data for a randomly selected sample of 366 schools, from across Australia's five more populous states. Interventions were offered by 52% of schools in the sample. Programs offered were grouped by theoretical emphasis for analysis. Constructivist interventions were most frequently offered, followed by cognitive, and other, programs. Statistically significant differences in the frequency and types of interventions offered were identified between states and sectors. An increase in cognitively oriented interventions and programs for small groups of students was identified. These findings are discussed in relation to policy documents and research literature. Recommendations are made for research into schools' intervention choices, the longitudinal impact of particular programs, and provision for students with more complex literacy difficulties.